2019
DOI: 10.5505/anatoljfm.2019.58077
|View full text |Cite
|
Sign up to set email alerts
|

Awareness Regarding Pelvic Organ Prolapse Among Women Attending A Teaching Hospital In Chitwan

Abstract: Pelvic organ prolapse is the descent of one or more of the pelvic structures from the normal anatomic location toward or through the vaginal opening influencing the quality of life of women particularly among adults and old women in developing countries. We aim to assess the awareness regarding pelvic organ prolapsed among women attending in a teaching hospital, Chitwan so that necessary awareness program could be recommended if found unsatisfactory. Methods: A descriptive cross-sectional study was done among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
(13 reference statements)
0
0
0
Order By: Relevance
“…College study, which found that less than half of respondents (42.5%) and more than half (57.5%) had adequate knowledge of haemorrhoids (Thapa and Author, 2019). A study conducted in the surgical OPD of CMCTH (2013) produced mixed findings, with less than half (48%) of respondents having insufficient degree of expertise and more over half 52 percent having acceptable information concerning haemorrhoids (Thapa and Author, 2019).…”
Section: Employmentmentioning
confidence: 99%
“…College study, which found that less than half of respondents (42.5%) and more than half (57.5%) had adequate knowledge of haemorrhoids (Thapa and Author, 2019). A study conducted in the surgical OPD of CMCTH (2013) produced mixed findings, with less than half (48%) of respondents having insufficient degree of expertise and more over half 52 percent having acceptable information concerning haemorrhoids (Thapa and Author, 2019).…”
Section: Employmentmentioning
confidence: 99%